2011
DOI: 10.1371/journal.pone.0028973
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Melanoma Cross-Resistance to BRAF and MEK Inhibitors by Co-Targeting the AKT/mTOR Pathway

Abstract: BackgroundThe sustained clinical activity of the BRAF inhibitor vemurafenib (PLX4032/RG7204) in patients with BRAFV600 mutant melanoma is limited primarily by the development of acquired resistance leading to tumor progression. Clinical trials are in progress using MEK inhibitors following disease progression in patients receiving BRAF inhibitors. However, the PI3K/AKT pathway can also induce resistance to the inhibitors of MAPK pathway.Methodology/Principal FindingsThe sensitivity to vemurafenib or the MEK in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(198 citation statements)
references
References 30 publications
8
188
2
Order By: Relevance
“…Our results predict that inhibitors of the PI3K pathway may restrain the expansion of tumors with mutations in BRAF at least in part through restoration of OIS features, a concept that is receiving increasing interest (Nardella et al 2011). Furthermore, in agreement with previous data (Shao and Aplin 2010;Atefi et al 2011;Paraiso et al 2011), we show that inhibition of PI3K can enhance the cytotoxicity of targeted BRAF V600E inhibition. In particular, the observation that a PI3K inhibitor can eliminate melanoma cells that resist killing by a BRAF V600E inhibitor is of obvious interest and merits further investigation.…”
Section: Ink4asupporting
confidence: 90%
See 1 more Smart Citation
“…Our results predict that inhibitors of the PI3K pathway may restrain the expansion of tumors with mutations in BRAF at least in part through restoration of OIS features, a concept that is receiving increasing interest (Nardella et al 2011). Furthermore, in agreement with previous data (Shao and Aplin 2010;Atefi et al 2011;Paraiso et al 2011), we show that inhibition of PI3K can enhance the cytotoxicity of targeted BRAF V600E inhibition. In particular, the observation that a PI3K inhibitor can eliminate melanoma cells that resist killing by a BRAF V600E inhibitor is of obvious interest and merits further investigation.…”
Section: Ink4asupporting
confidence: 90%
“…Although, initially, dramatic responses are seen in melanoma patients, eventually, most of them show tumor progression. Intense investigations have revealed that tumor relapse occurs owing to a variety of resistance mechanisms, some of them implicating activation of the PI3K pathway as a key player in resistance to BRAF or MEK inhibition (Shao and Aplin 2010;Atefi et al 2011;Paraiso et al 2011). Therefore, there is a dire need to find combination therapy to delay or avoid resistance.…”
Section: Pharmacologic Pi3k Inhibition Enhances Cytotoxicity Of Brafmentioning
confidence: 99%
“…It has recently been demonstrated that cotargeting of the MEK/ERK and PI3K/mTOR pathways with MEKi+AKTi and MEKi+mTORi 1 is effective in BRAF mutant cells with acquired resistance to BRAF inhibitors due to activating mutations in NRAS (26,27). Although these combinations also decreased cell growth in our panel of 10 human NRAS mutant melanoma cell lines, we observed that it was less effective in decreasing cell viability than MEKi+PI3K/mTORi 1,2 .…”
Section: Discussionmentioning
confidence: 58%
“…Beyond monotherapy, Nature Reviews | Clinical Oncology a growing body of literature supports the existence of positive mechanistic interactions of MEK inhibitor with cyclindependent kinases 4 and 6 (CDK4/6) inhibitors 73 , MDM2 antagonists 74 , or PI3K/AKT-pathway inhibitors 75 , leading to phase I and II trials investigating these combinations.…”
Section: Braf-targeted Therapiesmentioning
confidence: 99%